2020
DOI: 10.1111/ddg.14292
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity reactions to non‐steroidal anti‐inflammatory drugs (NSAIDs) – a retrospective study

Abstract: Background: The aim of this study was to verify the validity of clinical history and oral provocation challenges of patients with NSAID hypersensitivity and to identify safe alternatives. The COX-2 inhibitor etoricoxib, in particular, was studied. Patients and methods: In all, 104 patients with confirmed diagnoses of NSAID hypersensitivity treated at the Department of Dermatology, Frankfurt University Hospital, Germany between 2004 and 2012 were retrospectively studied. Results: The medical history and hyperse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
1
5
1
Order By: Relevance
“…A total of 59 (43.7%) patients reported symptoms to 2 or more chemically unrelated drugs. This is in accordance with the data delivered by Demir et al [14], who reported a cross-reactivity of 50.3% in a cohort of patients with NSAID-induced hypersensitivity reactions, and by Angeletti et al [13] whose group reported a 60.6% of patients who developed symptoms to more than one NSAID. In another study [12], only about a quarter of the patients reported the same reactions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A total of 59 (43.7%) patients reported symptoms to 2 or more chemically unrelated drugs. This is in accordance with the data delivered by Demir et al [14], who reported a cross-reactivity of 50.3% in a cohort of patients with NSAID-induced hypersensitivity reactions, and by Angeletti et al [13] whose group reported a 60.6% of patients who developed symptoms to more than one NSAID. In another study [12], only about a quarter of the patients reported the same reactions.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we evaluated 135 patients, of which 80% were female, a percentage higher than in other studies. [12,13]. Although in other studies [14] atopy was more frequently encountered among patients with NSAIDinduced DHR, in our cohort only 1 in 7 patients had a positive skin test to house dust mites or pollens.…”
Section: Discussioncontrasting
confidence: 47%
“…Inclusion criteria for the patients were as follows: Diagnosis of cross-hypersensitivity ( Pérez-Alzate et al, 2017 ; Blanca-López et al, 2018 , Blanca-López et al, 2019 ) by clinical history and a positive drug provocation test, for one or more of the following NSAIDs: ibuprofen, diclofenac, aceclofenac, indomethacin, naproxen, piroxicam, meloxicam, lornoxicam, celecoxib, and metamizole. ASA-positivity was included as a requisite in the diagnosis because in cross-reactive (non-allergic) hypersensitivity patients react to all strong COX-1 inhibitors, including ASA, whereas allergic hypersensitivity patients tolerate ASA ( Kowalski et al, 2013 ; Pérez-Alzate et al, 2017 ; Angeletti et al, 2020 ); besides, CYP2C9 plays a role in ASA metabolism ( Thiessen, 1983 ; Hutt et al, 1986 ; Bigler et al, 2001 ; Palikhe et al, 2011 ; Gómez-Tabales et al, 2020 ). Patients who presented with hypersensitivity triggered by other NSAIDs whose metabolism is not mainly catalyzed by CYP2C enzymes (including clonixinate, dexketoprofen, ketorolac, etofenamate, ketoprofen, piketoprofen, propifenazone, phenylbutazone, aminophenazone, acetaminophen, etoricoxib and oxyphenbutazone) were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Cutaneous adverse drug reactions include a significant proportion of all adverse drug reactions, most ascribed to the use of non-steroidal anti-inflammatory drugs [1,2]. The majority are neither severe nor life-threatening; instead, rare but life-threatening severe cutaneous adverse reactions, such as TEN or Lyell syndrome (LS), Stevens-Johnson syndrome (SJS), acute generalized exanthematous pustulosis (AGEP), and drug reaction with eosinophilia and systemic symptoms (DRESS), are associated with important systemic involvement.…”
Section: Clinical Lettermentioning
confidence: 99%